2021
DOI: 10.12688/wellcomeopenres.16576.1
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine hesitancy in an ethnically diverse community: descriptive findings from the Born in Bradford study

Abstract: Background: The roll out of coronavirus disease 2019 (COVID-19) vaccines are now underway in the UK, and ensuring good uptake in vulnerable communities will be critical to reducing hospital admissions and deaths. There is emerging evidence that vaccine hesitancy is higher in ethnic minorities and deprived areas, and that this may be caused by misinformation in the community.  This study aims to understand COVID-19 vaccine hesitancy in an ethnically diverse and deprived population. Methods: Questionnaire survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 8 publications
5
25
0
Order By: Relevance
“…Recent work by Bell et al found that parents from ethnic minority backgrounds other than White in the UK are less likely to accept a COVID-19 vaccine for their children (14). This finding is consistent with other reports that individuals from ethnic minorities are less likely to accept COVID-19 vaccination for themselves (15,16). For example, initial analysis of the UK's COVID-19 vaccine program for adults aged over 80 years found lower uptake among Black Afro-Caribbean ethnicities (17).…”
Section: Introductionsupporting
confidence: 79%
“…Recent work by Bell et al found that parents from ethnic minority backgrounds other than White in the UK are less likely to accept a COVID-19 vaccine for their children (14). This finding is consistent with other reports that individuals from ethnic minorities are less likely to accept COVID-19 vaccination for themselves (15,16). For example, initial analysis of the UK's COVID-19 vaccine program for adults aged over 80 years found lower uptake among Black Afro-Caribbean ethnicities (17).…”
Section: Introductionsupporting
confidence: 79%
“…The social care workforce is predominately female (82%, compared to 47% in the economically active population), and with a higher proportion of BAME individuals (21% vs 14% in England) [14]. This is a similar demographic to the parts of the general population with high levels of COVID-19 vaccine hesitancy [15,16,17]. Concerns about the lack of adequate research into vaccine safety were widespread and were the most prevalent reason for non-vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns about the lack of adequate research into vaccine safety were widespread and were the most prevalent reason for non-vaccination. These mirror concerns of the general population [15,16,17]. Strategies to quell these specific fears need to utilise personal experience alongside expert advice, in order to be successful [19].…”
Section: Discussionmentioning
confidence: 99%
“…These concerns over the safety of the vaccine were heightened by media reports and the negative experiences of others. Previous research [10,11] has highlighted concerns over lack of research and a perception vaccine development had been rushed, as reasons for people not getting a COVID-19 vaccine. Participants in the current study reported they would consider getting the vaccine in the future once they perceived it to be effective and safe.…”
Section: Barriers To Getting the Vaccinementioning
confidence: 99%
“…Research has identified several barriers to getting the COVID-19 vaccine, including mistrust in healthcare professionals and scientists, safety concerns, negative perceptions of vaccination side effects, lower perceived threat of COVID-19, and inconsistent information [11][12][13][14][15]. Barriers for care home employees include perceived lack of research, concerns over fertility, concerns over allergic reactions, and difficulty accessing vaccination appointments [10], with similar barriers also being identified among healthcare workers [16].…”
Section: Introductionmentioning
confidence: 99%